Three-dimensional concrete impact and penetration simulations using the smoothed particle Galerkin method. (August 2017) - Wu, C.T.; Wu, Youcai; Crawford, John E.; Magallanes, Joseph M.
Highlights: Three dimensional smooth particle Galerkin formulation is presented. An adaptive anisotropic Lagrangian kernel is utilized. A bond-based failure criterion is introduced. A frictionless self-contact algorithm has been developed. Numerical results are validated with test data for high velocity impact penetration on concrete structures. Abstract: In this paper, we model the three-dimensional concrete impact and penetration problems using a stabilized meshfree method. The present method is established using a non-residual penalty term from strain smoothing as a means of stabilizing the meshfree nodal integration method under the Galerkin framework. As a result, the meshfree discretization leads to a dual stress point algorithm with the stabilization parameterized by a measure of a local length scale. An adaptive anisotropic Lagrangian kernel is considered in junction with the stabilized meshfree formulation for the severe deformation analysis. In order to avoid the spurious damage growth and material self-healing in concrete failure analysis, a bond-based failure criterion is introduced. A frictionless self-contact algorithm is also developed to model the interaction between concrete debris in damage. Several impact examples are investigated including the study of scabbing and perforation of concrete under high velocity impact. The numerical results are compared with the experimental data to demonstrate the effectiveness of the present method.